-7(3q-1)=expand

Simple and best practice solution for -7(3q-1)=expand equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(3q-1)=expand equation:


Simplifying
-7(3q + -1) = expand

Reorder the terms:
-7(-1 + 3q) = expand
(-1 * -7 + 3q * -7) = expand
(7 + -21q) = expand

Solving
7 + -21q = adenpx

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -21q = -7 + adenpx

Combine like terms: 7 + -7 = 0
0 + -21q = -7 + adenpx
-21q = -7 + adenpx

Divide each side by '-21'.
q = 0.3333333333 + -0.04761904762adenpx

Simplifying
q = 0.3333333333 + -0.04761904762adenpx

See similar equations:

| 5x+76x=105 | | 2y+4+3y-5+y=29 | | 0.88*x=22 | | z^2+12=48 | | log(128)4=x | | (3x)^2/3=0 | | 18-x/3=16 | | (x^2)=80 | | (3x-2)^2/3=16 | | -(4/7)-(1/5) | | x+2/13=9/13 | | (x^2)=-45 | | 2w^3-32w^2+6w-16= | | -4-7V=-26/3 | | 6.27=y/2.5-9.8 | | (6e+4*64)*500/63 | | -5/8/6 | | 3x+4=91 | | 8/7(-4)-8 | | -4x-3=-4x+1 | | 2.4(a+0.5)=-0.8(a+1.5) | | 2y^2+-2y+6y+-6=0 | | (6e+4*94)+7/9 | | 24/7-8 | | 6x=-5/8 | | (x^2)=72 | | 6(8.66+4)=3(8.66)-2 | | 7/8-1/4+3/4x=1/16+x | | x=4+0.5y | | b^2+6b-4=0 | | -8e+16=28-4e | | 3/8+5=20 |

Equations solver categories